Analysis precision of joint pain in Apotek Kimia Farma Mejasem Tegal - Shellma Noor Aida; Heru Nurcahyo; Joko Santoso (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2021)
This research aims to find out and analyze the accuracy of self-medication for joint pain in the community, especially those who buy drugs at the Apotek Kimia Farma, Mejasem, Tegal. The sampling technique in this study uses the purposive sampling method, which determines sampling by determining specific characteristics according to the research objectives so that it is expected to answer the research problem. This research is classified into descriptive research, namely research with a method to make a systematic description of the accuracy of self-medication for joint pain in the community who visited the Apotek Kimia Farma Mejasem. The instruments used in this study were demographic data and questionnaires. The work steps used in data collection in this study used interview techniques guided by the questionnaire. The results of the study were as follows, community self-medication in joint pain showed the correct percentage of people with an indication of 85%, the percentage of people who were right in the group of 85%, the percentage of people who had the correct dose of 71%, and the percentage of people who were alert to drug side effects was 27%. In conclusion, most people who buy drugs at the Apotek Kimia Farma Mejasem were correct in self-medication for joint pain, except for the awareness of drug side effects. The percentage of people who had the correct dose was 71%, and the percentage of people alert to drug side effects was 27%.